Adaptive architecture : changing parameters and practice - Preiser, Wolfgang F. E.; Hardy, Andrea; Wilhelm, Jacob J. (Routledge, Taylor & Francis Group, 2018)
"The constant in architecture's evolution is change. Adaptive Architecture explores structures, or environments that accommodate multiple functions at the same time, sequentially, or at periodically recurring events. It demonstrates how changing technological, economic, ecological and social conditions have altered the playing field for architecture from the design of single purpose structures to the design of interacting systems of synergistically interdependent, distributed buildings. Including contributors from the US, UK, Japan, Australia, Germany and South Africa, the essays are woven into a five-part framework which provides a broad and unique treatment of this important and timely issue."